ANALYSIS OF THE APPLICATION OF STATEMENTS OF FINANCIAL ACCOUNTING STANDARDS 102 OF MURABAHAH FINANCING TRANSACTIONS AT SHARIA PEOPLE’S FINANCING BANKS OF HARTA INSAN KARIMAH OF MAKASSAR - Nurbayani, Nurbayani; Rahman, Abdul; Wahyuni, Sri (Jurnal Iqtisaduna, 2019)
This study aims to analyze and obtain empirical evidence of the suitability of PSAK 102 with the accounting treatment of murabahah contracts at Sharia People’s Financing Banks (SPFB) of Harta Insan Karimah (HIK) of Makassar. Comparative descriptive study is a type of research that the author analyzes the comparison of Murabahah contract accounting treatment at SPFB of HIK with accounting treatment based on PSAK 102. The results of the research show that most murabahah contract accounting is following PSAK 102, but not completely. The appropriate treatment is the presentation and disclosure, while in the recognition and measurement there are still some accounting treatments that have not been applied. This can be proved by the absence of murabaha asset accounting treatment, and advance accounting treatment, but the SPFB of HIK imposes and receives fees such as notary fees, insurance fees, stamp duty, and recognizes them as deposit fees and administrative costs.